Further Advances on Soil Microarthropod Community Testing for the Risk Assessment of Plant Protection Products. - Campos, Pedro Miguel Sotaia (2020)
Dissertação de Mestrado em Biologia apresentada à Faculdade de Ciências e Tecnologia